2014
DOI: 10.1016/b978-0-444-63456-6.50162-9
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds Number Effects on Particle Agglomeration in Turbulent Channel Flow

Abstract: The work described in this paper employs large eddy simulation and a discrete element method to study particle-laden flows, including particle dispersion and agglomeration, in a horizontal channel. The particle-particle interaction model is based on the HertzMindlin approach with Johnson-Kendall-Roberts cohesion to allow the simulation of Van der Waals forces in a dry air flow. The influence of different flow Reynolds numbers, and therefore the impact of turbulence, on particle agglomeration is investigated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In 2015, they further investigated particle deposition and resuspension behavior in gas-cooled reactors (Barth et al 2015). In addition, Afkhami et al (2014Afkhami et al ( , 2015 employed LES and the discrete element method to study particle dispersion and agglomeration behavior in a horizontal channel flow and concluded that both particle-particle interactions and Reynolds number have a significant effect on these particle behaviors across the flow Reb range considered (2100-8260). Li et al (2016) also used direct numerical simulation to study particleflow turbulence interaction in the wall region of a flat plate boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, they further investigated particle deposition and resuspension behavior in gas-cooled reactors (Barth et al 2015). In addition, Afkhami et al (2014Afkhami et al ( , 2015 employed LES and the discrete element method to study particle dispersion and agglomeration behavior in a horizontal channel flow and concluded that both particle-particle interactions and Reynolds number have a significant effect on these particle behaviors across the flow Reb range considered (2100-8260). Li et al (2016) also used direct numerical simulation to study particleflow turbulence interaction in the wall region of a flat plate boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…Turbulence and agitation may also result in re-agglomeration of particles [25]. Further, it is to be noted that the flow velocities can effect segregation, depending on the local flow patterns.…”
Section: Supplementary Video#1mentioning
confidence: 99%